An Exome Sequencing Study to Assess the Role of Rare Genetic Variation in Pulmonary Fibrosis - Petrovski, Slavé (Am J Respir Crit Care Med, 2017)
Rationale: Idiopathic pulmonary fibrosis (IPF) is an increasingly recognized, often fatal lung disease of unknown etiology. Objectives: The aim of this study was to use whole-exome sequencing to improve understanding of the genetic architecture of pulmonary fibrosis. Methods: We performed a case–control exome-wide collapsing analysis including 262 unrelated individuals with pulmonary fibrosis clinically classified as IPF according to American Thoracic Society/European Respiratory Society/Japanese Respiratory Society/Latin American Thoracic Association guidelines (81.3%), usual interstitial pneumonia secondary to autoimmune conditions (11.5%), or fibrosing nonspecific interstitial pneumonia (7.2%). The majority (87%) of case subjects reported no family history of pulmonary fibrosis. Measurements and Main Results: We searched 18,668 protein-coding genes for an excess of rare deleterious genetic variation using whole-exome sequence data from 262 case subjects with pulmonary fibrosis and 4,141 control subjects drawn from among a set of individuals of European ancestry. Comparing genetic variation across 18,668 protein-coding genes, we found a study-wide significant (P < 4.5 × 10(−7)) case enrichment of qualifying variants in TERT, RTEL1, and PARN. A model qualifying ultrarare, deleterious, nonsynonymous variants implicated TERT and RTEL1, and a model specifically qualifying loss-of-function variants implicated RTEL1 and PARN. A subanalysis of 186 case subjects with sporadic IPF confirmed TERT, RTEL1, and PARN as study-wide significant contributors to sporadic IPF. Collectively, 11.3% of case subjects with sporadic IPF carried a qualifying variant in one of these three genes compared with the 0.3% carrier rate observed among control subjects (odds ratio, 47.7; 95% confidence interval, 21.5–111.6; P = 5.5 × 10(−22)). Conclusions: We identified TERT, RTEL1, and PARN—three telomere-related genes previously implicated in familial pulmonary fibrosis—as significant contributors to sporadic IPF. These results support the idea that telomere dysfunction is involved in IPF pathogenesis.